Can negative characters in soap operas be positive for product placement? - Dias, J. A.; Dias, J. G.; Lages, C. (Journal of Business Research, 2017)
The purpose of this study is twofold: (1) to test how the consumer's attitude toward product placements in a television soap opera is affected by the use of different types of character: positive versus negative; and (2) to determine the circumstance in which a negative character can be appropriated in product placement The conceptual model proposes that the attitude toward product placement in general has a direct and indirect impact on the attitude toward the placed product, while the (negative or positive) nature of the television characters interacting with the placed product works as a moderator. Experimental data test the model. The stimuli were original product placements in a soap opera broadcast Results from a structural equation model show that negative characters can be effective vehicles for product placement as long as viewers meet two conditions: they manifest general acceptance of product placement and have a parasocial relationship with the character.